2020
DOI: 10.1128/mbio.01723-20
|View full text |Cite
|
Sign up to set email alerts
|

Can Dietary Fatty Acids Affect the COVID-19 Infection Outcome in Vulnerable Populations?

Abstract: There is high mortality in coronavirus disease 2019 (COVID-19)-infected individuals with chronic inflammatory diseases, like obesity, diabetes, and hypertension. A cytokine storm in some patients after infection contributes to this mortality. In addition to lungs, the intestine is targeted during COVID-19 infection. The intestinal membrane serves as a barrier to prevent leakage of microorganisms and their products into the bloodstream; however, dietary fats can affect the gut microbiome and may increase intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…Thus, the presence of a low-grade chronic inflammatory state in individuals with a dysregulated metabolic state, which is at least partly explained by gut dysbiosis, could increase the risk of greater COVID-19 severity and morbidity ( 67 ). As suggested by Onishi et al ( 68 ), it would also be interesting to further investigate the implication of microbial-derived endotoxins in determining the severity of the cytokine storm in people with pre-existing metabolic comorbidities. Recent work from our group showed that bacteria or microbial components can cross the intestinal barrier in morbidly obese individuals ( 69 ).…”
Section: The Contribution Of the Gut Microbiota To Chronic Low-grade Inflammation In Assessing Covid-19 Severitymentioning
confidence: 96%
“…Thus, the presence of a low-grade chronic inflammatory state in individuals with a dysregulated metabolic state, which is at least partly explained by gut dysbiosis, could increase the risk of greater COVID-19 severity and morbidity ( 67 ). As suggested by Onishi et al ( 68 ), it would also be interesting to further investigate the implication of microbial-derived endotoxins in determining the severity of the cytokine storm in people with pre-existing metabolic comorbidities. Recent work from our group showed that bacteria or microbial components can cross the intestinal barrier in morbidly obese individuals ( 69 ).…”
Section: The Contribution Of the Gut Microbiota To Chronic Low-grade Inflammation In Assessing Covid-19 Severitymentioning
confidence: 96%
“…However, diarrhea and flatulence are the most frequent side-effects to acarbose, due to its inhibition of starch digestion [ 191 ] and fibre can lead to similar gastrointestinal problems [ 190 ]. It has been suggested that when the COVID-19 infection involves the intestine of obese individuals, dysbiosis could contribute to the cytokine storm [ 192 ]. Dietary fats induce dysbiosis and may increase intestinal permeability, inducing endotoxemia and chronic low-grade inflammation [ 192 ], whereas polyphenols modulate microbiota composition [ 186 ].…”
Section: Mechanisms Of the Mediterranean Diet Componentsmentioning
confidence: 99%
“…It has been suggested that when the COVID-19 infection involves the intestine of obese individuals, dysbiosis could contribute to the cytokine storm [ 192 ]. Dietary fats induce dysbiosis and may increase intestinal permeability, inducing endotoxemia and chronic low-grade inflammation [ 192 ], whereas polyphenols modulate microbiota composition [ 186 ]. Although antiviral properties against SARS-CoV-2 (related to virus entry into the cells) have been reported in vitro for some bioactive phytochemicals ( Figure 1 ), including the hesperidin [ 193 , 194 ], quercetin [ 194 , 195 ], kaempferol [ 194 ], catechins [ 194 , 196 ], baicalin [ 197 ], curcumin [ 194 ] and resveratrol [ 194 ], their availability in humans is low [ 198 ].…”
Section: Mechanisms Of the Mediterranean Diet Componentsmentioning
confidence: 99%
“…At that point of time, there were only three papers (e-published during April or May, 2020) that mentioned the possibility of a link between diet and Covid-19, in passing. [137][138][139][140] During the 13 months that have passed since, numerous other papers have also noted connections between Covid-19 and diet, nutrition, microbiomes, dysbiosis, immunity, or inflammation, [141][142][143][144][145][146][147][148][149][150] including one paper that happened to cite the original preprint on Research Gate. [151] However, none of these earlier, or subsequent, papers explicitly holds chronic inflammation (CHRi) to be the cause of the proposed rapid rise and slow abatement of acute inflammation (ACUi), or the proposed spiralling of ACUi into hyper-inflammation (HYPI), as proposed in this paper.…”
Section: Other Recent Relevant Literaturementioning
confidence: 99%